Answer:
y = 1/9
Step-by-step explanation:
(-2, y) = (x, y)
y = 3^x
y = 3^(-2)
y = 1/9
Therefore y = 1/9
TABLE / BOX
| h ||||||| 0 | 1 | 2 | 3 | 5 | 9 | 12 | 13 | 15
| M(h) | 0| .1/.5 |.2/.5|.3/.5| 1 |1.8|2.4| 2.6| 3
I tried my best on putting it in order sorry if its not clear
make shure to put brainliest!
<span>Ending Amt = Bgng Amt * e ^-0.03t
In this equation, the "-0.03" is the decay factor or "k"
We can now solve for half-life by this equation:
</span>t = <span>(<span>ln [y(t) ÷ a]<span>)<span> ÷ -k (we can say beginning amount = 200 and ending amount = 100
</span></span></span></span>t = <span>(<span>ln [200 ÷ 100]<span>)<span> ÷ -k
</span></span></span></span>t = <span>(<span>ln [2]<span>)<span> ÷ -k
</span></span></span></span>t = 0.69314718056<span> ÷ --.03
t =</span><span><span><span> 23.1049060187
</span>
about 23 years
</span></span>
Answer:
16 and 17
Step-by-step explanation:
16 * 17 = 272